The activities of Jewish political parties in Poland during 1918-1926 - Evhen Gorb (Cхід, 2013)
The position of the Jewish minority in the political life of the Second Polish Republic was markedly different from that of other ethnic minorities. The Polish authorities to restrict, and even suppress the activity of Jewish political organizations. In the inter-war Poland were five main areas of the political movement of the Jewish community - assimilation, orthodox, Zionist, socialist and folkists. Assimilators treated Jews as an integral part of the Polish people. They were fully committed to the ideals of the Polish national liberation movement. Party orthodox direction characterized by protection of the rights of Judaism, the educational activities, a certain degree of conservatism (due to the fact that the religious factor they have always dominated the political).The main feature of the Zionists had the idea of creating an autonomous (or independent) of a Jewish state in Palestine. Jewish socialists predominantly showed solidarity with the Polish workers movement. Folkists Party of the main backbone of the ideology have done thesis on national-personal autonomy of Polish Jews.